Is DHT Production by 5α-Reductase Friend or Foe in Prostate Cancer? - Kosaka, Takeo; Miyajima, Akira; Oya, Mototsugu (Frontiers in Oncology, 2014)
The first advance in the history of studies on prostate cancer and androgens was the development of treatment with castration and administration of estrogen by Charles B Huggins, who won the Nobel Prize in Physiology and Medicine. Since then, and for 70 years, androgen deprivation therapy (ADT) has been the standard therapy for advanced prostate cancer and the center of studies on prostate cancer (PCa). However, recent advances have shed light on the relationship between androgens and the development or the progression of PCa. The use of 5AR inhibitors to prevent progression of PCa continues to be widely discussed. Discussion has been fueled by the findings of two large randomized, placebo-controlled trials: the Prostate Cancer Prevention Trial (PCPT) with finasteride and the Reduction by Dutasteride of Prostate Cancer Events (REDUCE) trial. Does the development of prostate cancer or progression to castration resistant prostate cancer depend on DHT? Here we summarize and discuss recent topics of local androgen production of DHT in prostate cancer.